Theorising Disability Care (Non-)Personalisation in European Countries: Comparing Personal Assistance Schemes in Switzerland, Germany, Sweden, and the United Kingdom - Christoph Tschanz (Social Inclusion, 2018)
This article examines four European countries (Switzerland, Germany, Sweden, and the United Kingdom) with respect to their degree of disability care personalisation. The approach is embedded in a broader theoretical analysis, which in turn is inspired by the notion of bivalent social justice as presented by Nancy Fraser (2003). The theoretical argument is that claims for personal assistance are part of a broader movement toward emancipation. However, it is argued that the specific settings of welfare regimes provide structures that empower or mitigate the possible implementation of personal assistance schemes. The author argues that conservative-corporatist welfare regimes provide less-supportive opportunity structures for policy change pertaining to personal assistance than other welfare regimes. This heuristic argument is developed further by looking more closely at key figures of Sweden, Germany, and the United Kingdom as being ideal-typical welfare regime cases. Furthermore, the case of Switzerland is outlined in an in-depth manner as it seems to have conservative-corporatist characteristics regarding the organisation of disability care while simultaneously being difficult to theorise. It is the aim of this article to serve as a first heuristic undertaking for analysing the low level of disability care personalisation in certain continental European cases.